INCOME OF THE POPULATION AND LIVING STANDARDS IN UZBEKISTAN (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
The article presents elaborated conclusions and proposals on the current state of living standards of the population of the country and its further improvement.